Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 3166 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Xenopus laevis (Daudin, 1802)", "HasCoordinate is true" ] } The dataset includes 3166 records from 32 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000281-150422101436696/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences